Malaysian and Nigerian university students' behavioral intention to adopt green computing : an invariance analysis - Bello, Abdullahi (Kulliyyah of Education, International Islamic University Malaysia, 2019)
This study is an attempt to empirically examine the dimensions that influence Malaysian and Nigerian university students' intention to adopt green computing practices. Using Ajzen's (1992) extended Theory of Planned Behaviour, knowledge was added to the existing three constructs (i.e. attitude, subjective norm, perceived behavioural control) as a predictor variable. The survey data were drawn from 1,262 university students in selected universities in Malaysia and Nigeria. Principal components analysis (PCA) and confirmatory factor analysis (CFA) using AMOS version 16 were run to assess the dimensionality and validity of the main constructs, namely attitude, subjective norm, perceived behavioural control and knowledge. Structural equation modeling (SEM) was used to test the four hypotheses formulated for the study. The results found that attitude, subjective norm, perceived behavioural control and knowledge collectively and individually exerted positive influences on students' intention to adopt green computing practices, while knowledge influenced intention and engagement in green computing. The results, therefore, justified the extension of the TPB theory with knowledge as an additional predictor variable. The study also established significant differences in intention to practice green computing between the two student samples, with Malaysian students expressing a greater intention to do so.